PECULIARITIES OF CLINICAL MANIFESTATIONS AND BIOELECTRICAL PARAMETERS IN CHILDREN AND ADOLESCENTS WITH OPTIMISATION OF PROPER NUTRITION (World Bulletin of Public Health, 2024)
Epilepsy remains today the most common chronic disease of the nervous system in children and adolescents. Within the last two centuries, significant milestones have been made towards a better understanding of the multifarious aspects of what was once considered a ‘sacred disease’.
Keywords: bioelectrical parameters; children; adolescents; proper nutrition